Hubungan Pengetahuan Ibu Terhadap Pemberian ASI Ekslusif - Kamila, Nurul Auliya; Suryatim Pratiwi, Yopi (STIKES Yarsi Mataram, 2024)
Background: Breast milk is the first natural food for babies during the first six months of life which meets the baby's nutritional needs for optimal growth, development and health. There are various factors that influence exclusive breastfeeding, including the mother's knowledge about exclusive breastfeeding. Research objective: To determine the relationship between maternal knowledge and exclusive breastfeeding in the Cakranegara Health Center. Research design: the type of research used is quantitative research with a descriptive correlation design with a cross sectional approach. The population in this study was 130 breastfeeding mothers. Data analysis used the chi-square test. Research results: Characteristics of respondents, mostly aged between 20-35 years, totaling 44 people (88.0). 26 people (52.0%) had completed high school education, 17 people (34.0%) worked as traders. Meanwhile, 6 people had good knowledge about exclusive breast milk (12.0%), 14 people had good knowledge about exclusive breast milk (28.0%), 30 mothers had poor knowledge (60.0%). Meanwhile, there were 17 mothers who gave breast milk exclusively to their children (34.0%). There is a relationship between maternal knowledge and exclusive breastfeeding in the working area of the Cakranegara Community Health Center, with p value: 0.004 < a 0.005 so that Ho is rejected and Ha is accepted. Research Conclusion: There is a relationship between maternal knowledge and exclusive breastfeeding. Suggestion: There is a need for education regarding exclusive breastfeeding to the community in the Cakranegara Health Center.